2015
DOI: 10.1515/humor-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Put-Down Humor Directed at Outgroup Members Increases Perceived – but Not Experienced – Cohesion in Groups

Abstract: Put-down humor always has a target, and the intent of the speaker is to make fun of someone or something. Due to its inherently social nature, put-down humor could strongly affect socio-emotional group processes and outcomes like cohesion. We hypothesized that put-down humor would increase cohesion when it was targeted at outgroup members and was followed by laughter. Two laboratory experiments were conducted to examine the underlying processes of the put-down humor -cohesion relation. Study 1 showed that put-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, aggression by girls towards peers was related to in-and out-group belonging, defined within a specific Cook Islands context. In-and out-group aggression is not new and 'put-down humour' has been shown to be particularly effective in developing cohesion when targeting members of the out-group (Gockel and Kerr 2015). Christine Gockel and Norbit Kerr (2015) have also shown that put-downs using humour are even more effective when the group members are similar to each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, aggression by girls towards peers was related to in-and out-group belonging, defined within a specific Cook Islands context. In-and out-group aggression is not new and 'put-down humour' has been shown to be particularly effective in developing cohesion when targeting members of the out-group (Gockel and Kerr 2015). Christine Gockel and Norbit Kerr (2015) have also shown that put-downs using humour are even more effective when the group members are similar to each other.…”
Section: Resultsmentioning
confidence: 99%
“…In-and out-group aggression is not new and 'put-down humour' has been shown to be particularly effective in developing cohesion when targeting members of the out-group (Gockel and Kerr 2015). Christine Gockel and Norbit Kerr (2015) have also shown that put-downs using humour are even more effective when the group members are similar to each other. Thus, while aggression by girls towards their peers relating to in-and out-group status is not a novel phenomenon, the defining characteristics of the outsider are unique to the cultural context.…”
Section: Resultsmentioning
confidence: 99%
“…Although a tricky concept to define, the link between teasing and cohesion has been widely demonstrated (Keltner, Capps, Kring, Young & Heerey, 2001; Nesi, 2012; Pichler, 2006). Gockel and Kerr (2015), for instance, highlighted that group cohesion is enhanced through group members’ shared amusement at the expense of someone else out-with the group. This certainly relates to long-held group dynamics literature, which argues that members of groups are likely to see themselves as superior to others, and thus form bonds based on this shared unity (Tajfel & Turner, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Keltner, Capps, Kring, Young & Heerey, 2001;Nesi, 2012;Pichler, 2006). Gockel and Kerr (2015), for instance, highlighted that group cohesion is enhanced through group members' shared amusement at the expense of someone else out-with the group, which certainly relates to long-held group dynamics literature that advocates that members of groups are likely to see themselves as superior to others, and as such, form bonds based on this shared unity (Tajfel & Turner, Submission to special issue: "Problem-based learning (PBL) and psychology" Author pre-print version 14 1986). Here, Euan's uncertainty around the word "deets" -and the fact it is explained to him -is oriented to with laughter from both Rachel and Donald, before being made into a joke by Rachel who likens it to the brand 'Deet' insect repellent.…”
Section: Jaworkimentioning
confidence: 99%
“…Aside from the humour, laughter can be evoked through nervousness, surprise, affiliation, maliciousness, face-saving, or as a form of threatening action (O'Donnell-Trujillo and Adams 1983). Gockel and Kerr (2015) found that humour directed at outgroup members increases perceived cohesion in groups, although not necessarily actual experiences of cohesion.…”
Section: Humourmentioning
confidence: 99%